Professionalism in medicine in South Africa - a focus on medical students and their educators - Olckers, Lorna (Department of Public Health and Family Medicine, 2019)
The notion of ‘professionalism in medicine’ has become increasingly topical globally. It is a complex and ‘slippery’ concept that is variously understood – from ideas of values or virtues that reflect aspects of ‘being’, to those that are more closely associated with behaviour and aspects of ‘doing’. More recently, issues of ‘identity formation’ have added a third dimension to these two broad areas of understanding. The lack of a shared and coherent understanding of what actually constitutes professionalism has resulted in challenges with the teaching, learning and assessment of professionalism in medicine. This has been widely reflected, including within the medical curriculum at the University of Cape Town (UCT) in Cape Town, South Africa, which provides the context for this research. The aim of this study was to explore how medical students and their educators understand and experience professionalism in medicine in the South African (SA) context. The specific objectives in relation to professionalism in medicine were to explore how aspects of being or character are understood and experienced; how aspects of doing or practice are understood and experienced; how global and profession-specific changes have influenced its understandings and experiences; how the SA context is understood and experienced in relation to professionalism in medicine; and how it is understood and experienced within the Health Sciences Faculty at UCT. The research was framed within an interpretive theoretical paradigm in order to illuminate issues of context, difference and power. Qualitative methods, specifically focus groups and individual interviews, were used with participants including medical students studying at UCT, interns who had graduated from UCT, and educators from within the university. Results from the study revealed themes that were considered against physician and philosopher Dr Edmund Pellegrino’s virtue-based understanding of professionalism in medicine that shaped the conceptual framework for the study. Four key issues formed the focus of discussion – the understanding of professionalism; its development alongside emerging identity; its relationship to power and hierarchy; and the implications of context. Unlike the discrete vision of professionalism as embedded within virtues or values as expressed by Pellegrino, the understandings and experiences of study participants reflected a multi-faceted view of professionalism in medicine as a combination of values, knowledge and skills, behaviour, and responsibilities, linked to a core relationship founded on trust between doctors and patients. This understanding was informed by issues of emerging identity, influenced particularly by the ‘hidden curriculum’ and role models, as well as experiences of power and hierarchy within the university and practice settings. Contextual realities included the commercialisation of medicine, and the increasing impact of the internet and social media. The South African context, reflected by the healthcare system and patient population, further informed this multi-faceted understanding of professionalism in medicine. What became clear was that professionalism in medicine was understood and experienced by participants as complex in both theory and practice, and that curriculum design processes and medical practice must therefore be cognisant of the interdependence of the key issues.